A Comparative Study of Teachers’ Perception Towards Extracurricular Activities According to their Demographics in Giraffe English School Nanjing, China - Gu, Ailun; Ye, Yan; Kanjanaphoomin, Jane (Scholar: Human Sciences, 2019)
This study attempted to determine and compare the teachers’ perception towards extracurricular activities according to their demographics in Giraffe English school, Nanjing City, Jiangsu province, China. A total of 75 full time teachers got involved in this study during the academic year 2017. The researcher adopted the questionnaire based on Judith’s (1978) to determine teachers’ perception towards extracurricular activities of 2 indicators including inclusive activities and exclusive activities in Giraffe English School Nanjing China. The study found that the total teachers’ perception towards extracurricular activities were moderate. There were significant differences of teachers’ perception towards extracurricular activities among teachers with different gender, age, work experience and background of study in Giraffe English School.